Pulmonary haemorrhage following renal transplantation. Issue 1 (January 1995) - Khan, G A; Klapper, P
Abstract : The case history is presented of a 32 year old black man who developed haemoptysis leading to pulmonary haemorrhage and bilateral pulmonary infiltrates. He was found to have Kaposi's sarcoma of the lung with no evidence of skin or endobronchial lesions.